Service user engagement in quality improvement: applying the national involvement standards. Issue 5 (7th November 2016) - Green, Stuart A.; Evans, Liz; Matthews, Rachel; Jayacodi, Sandra; Trite, Jenny; Manickam, Anton; Evered, Rachel; Green, John; Williams, Joanna; Beveridge, Ed; Parker, Caroline; Tiplady, Bill
Abstract : Purpose: National and local policy supports the involvement of patients at all levels in the design, delivery and improvement of health services. Whilst existing approaches to support involvement have been described and disseminated, including the 4Pi National Involvement Standards, their application in quality improvement is rarely reported. The paper aims to discuss this issue. Design/methodology/approach: A quality improvement initiative within a mental health trust was developed with a multi-disciplinary team, including those with professional experience of delivering or improving care and those with lived experience. The aim of the initiative was to improve the physical health of inpatients within an acute mental health unit. This case study aims to describe how the integration of concepts from the 4Pi National Involvement Standards (Principles, Purpose, Presence, Process and Impact) provided a framework for engaging and involving service users. The case study also aims to describe how co-design was included within the 4Pi approach and supported the development of a tool to aid improving physical healthcare. Findings: The 4Pi National Involvement Standards provided a guiding framework for the involvement of service users within a quality improvement initiative. Value of the approach was realised through the co-design of a tool developed by service users, along with healthcare professionals, to facilitate discussion and support shared-decision making about inpatients' physical health. Practical implications: Identifying "ways that work" for service user involvement is crucial to move beyond the policy rhetoric or tokenistic involvement. Involvement in quality improvement initiatives can bring benefits both to services and the service users themselves. Originality/value: Whilst the 4PI approach is recognised as a useful framework for involvement, few examples exist of its practical applications within a quality improvement setting.